Multi-electron reactions for the synthesis of a vanadium-based amorphous material as lithium-ion battery cathode with high specific capacity. (15th March 2021) - Kong, Fanhou; Liang, Xue; Yi, Lanlin; Fang, Xiaohui; Yin, Zhongbin; Wang, Yulong; Zhang, Ruixiang; Liu, Longyang; Chen, Qing; Li, Minghan; Li, Changjiu; Jiang, Hong; et al.
Abstract: The vanadium-based amorphous electrode material can realize the valence state conversion and increase its specific capacity through the multi-electron reaction. We have obtained V2 O5 –Li3 PO4 glass with a strong reducing agent CaC2, realizing a multi-electron reaction of V 5+ to V 4+ and then to V 3+ in the model system. Moreover, we have explored the relationship between valence state, crystallinity, and conductivity limit to compare the cycle performances of amorphous glass batteries. The CaC2 content of 20%, V 4+ presented the dominating valence state with a content of 77.5%. VP-C20% exhibited a maximum specific capacity of 319.3 mAh g −1, and the specific capacity after 100 cycles was 280.3 mAh g −1, corresponding to a retention capacity of 87.8%. The electrochemical performance of amorphous vanadium oxide decreased with the increase of the LiV2 O5 's nanocrystallinity. Crystallinity and the controllable multi-electron reaction could provide an important reference for designing other new electrode materials with high capacity and long cycle life. Graphical abstract: Image 1 Highlights: Vanadium-based amorphous electrode material could realize valence state conversion. V 5+ was reduced to V 4+, then to V 3+ with CaC2, as reducing agent. V 4+ enhanced ion and electron transport and cycling stability. The performance decreased with the increase of LiV2 O5 's nanocrystallinity.